Factors Associated with Morbid Obesity among School-Aged Children in Phra Nakhon Si Ayutthaya Province - Athipongarporn, Athipat (Journal of Preventive Medicine Association of Thailand, 2020)
Nowadays, obesity is serious non-communicable disease in many countries. According to Thai Clinical Practice Guideline for Pediatric Obesity, over nutrition are categorized into o overweight, obesity and morbid obesity. There are many comorbidities and complications such as type 2 diabetes mellitus, hypertension and dyslipidemia. This study was cross-sectional study. We collected the data by questionnaire about demographic data and risk factor of obesity for 108 children in Child Diabetic and Nutrition Clinic (CDNC) in Phra Nakhon Si Ayutthaya Hospital and collected the data from 133 control group in Anuban Phra Nakhon Si Ayutthaya School. The aims of this study are to study about risk factors associated morbid obesity and obesity in school-aged children. This study shows factors related to morbid obesity and obesity are parenting with grandparent, cooking by grandparent and family with diabetic patient. The factors that statistically significant between case and control group are parenting with parent, cooking by parent, frequency of exercise (football or basketball or badminton) more than 30 minute per week and number of diabetic patient in family. This data may be useful for developing health policy in childhood obesity prevention, such as educating proper nutrition to parents and encourage exercise.